2013
DOI: 10.1016/j.ygcen.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an enzyme immunoassay for assessing adrenocortical activity and evaluation of factors that affect levels of fecal glucocorticoid metabolites in two New World primates

Abstract: Non-invasive methods to assess stress hormone output via fecal glucocorticoid metabolites (FGCMs) have become a powerful tool in behavioral studies and conservation biology because they allow exploring the link between behavior, an animal's socio-ecological environment and its adrenocortical activity. However, FGCM levels are influenced by numerous other factors which often confound their interpretation. Thus, before applying these methods, knowledge on the impact of these factors is important. In this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 86 publications
6
71
0
1
Order By: Relevance
“…For example, GC metabolism differs between sexes in mice, rats and other rodents, with males typically excreting higher concentrations than females, with exceptions [123,124,127,128], and the specific FGCMs excreted are sexand species-specific [123][124][125]. Quantification of circadian rhythm is difficult: FGCMs can show a diurnal rhythm mirroring that of circulating GCs, but this rhythm can only be documented in animals that defecate multiple times per day [124,126,127]. Intestinal transit time, which regulates FGCM excretion rate, is influenced by physical activity; rodents excrete GCs more rapidly during the active versus passive phases [123].…”
Section: (D) Limitations Of Current Methodsmentioning
confidence: 99%
“…For example, GC metabolism differs between sexes in mice, rats and other rodents, with males typically excreting higher concentrations than females, with exceptions [123,124,127,128], and the specific FGCMs excreted are sexand species-specific [123][124][125]. Quantification of circadian rhythm is difficult: FGCMs can show a diurnal rhythm mirroring that of circulating GCs, but this rhythm can only be documented in animals that defecate multiple times per day [124,126,127]. Intestinal transit time, which regulates FGCM excretion rate, is influenced by physical activity; rodents excrete GCs more rapidly during the active versus passive phases [123].…”
Section: (D) Limitations Of Current Methodsmentioning
confidence: 99%
“…We also found no age effect on fGCM concentrations. In contrast, glucocorticoid concentrations have been reported to be higher in older individuals in humans, chimpanzees, brown spider monkeys (Ateles hybridus), and red howlers (Alouatta seniculus) (Rimbach et al 2013;Seraphin et al 2008;Van Cauter et al 1996). An earlier study on orangutans found a small significant increase in fGCM concentrations with increasing age in females but not in male orangutans (Weingrill et al 2011).…”
Section: Effect Of Visitors On Stress Indicatorsmentioning
confidence: 99%
“…In the case of primates, physiological stress levels have been shown to increase in males during mating seasons as a consequence of high reproductive competition [28][34], but not in species where mate competition is low [22], [35], [36]. Females, on the other hand, have higher energetic demands during gestation and lactation and this may also lead to higher physiological stress [34], [37][41]. This seems to hold true despite the fact that, in primates, females have been shown to have lower energetic costs during reproductive stages than other mammals of similar size [42][44].…”
Section: Introductionmentioning
confidence: 99%